Speaking in subtitles : revaluing screen translation - Dwyer, Tessa, 1970- (Edinburgh University Press, 2017)
"Over 6000 different languages are used in the world today, but the conventions of 'media speak' are far from universal and the complexities of translation are rarely acknowledged by the industry, audiences or scholars. Redressing this neglect, Speaking in Subtitles argues that the specific contingencies of translation are vital to screen media's global storytelling. Looking at a range of examples, from silent era intertitling to contemporary crowdsourced subtitling, and from avant-garde dubbing to the increasing practice of ́'fansubbinǵ', Tessa Dwyer proposes that screen media itself is a fundamentally ́'translational' field."--Google Books, November 26, 2019